Development of a nanomaterial-based electrochemical immunosensor for detection of aflatoxin B1 in peanuts - Azri, Farah Asilah (2016)
Aflatoxin B1 is epidemiologically implicated as carcinogen in humans due to contamination in several agricultural commodities either pre- or post-harvest under favourable conditions of temperature and humidity. Development of rapid and sensitive method for detecting aflatoxin B1 is important for food safety and quality to minimise the exposure of this toxin towards consumers. In this study, the use of multi-walled carbon nanotube (MWCNT) with chitosan (CS) was investigated as a modifier on the screen-printed carbon electrode (SPCE). The modification of electrode was studied as a platform to fabricate the immunoassay for further electrochemical reaction to occur. MWCNT was first successfully functionalised via strong acid treatment (H2SO4:HNO3) by adding carboxylic acid (-COOH) groups and increased the MWCNT’s surface area. The characterisation was done by FTIR and the additional group was confirmed by the presence of peak at 1715 cm-1 and shorter nanotube can be seen through FESEM. Based on the electrochemical analysis, the modification of SPCE with the functionalised MWCNT greatly enhanced the current response up to 7 times. The modification of SPCE was optimised through various parameters, which includes pH, scan rate, MWCNT ratio, drop coating volume and drying condition. Ten microliters of MWCNT:CS (with mixing ratio, 5:1) for electrode coating and oven dried for 10 minutes at 80⁰C were optimal for electrode casting. Furthermore, the electrochemical scan was done under 0.1 Vs-1 of scan rate and PBS pH7 was used throughout this study. An indirect competitive ELISA was optimised prior to transferring onto the modified electrode. Through checkerboard study, the concentration of AFB1-BSA at 0.25 μg/mL and anti-AFB1 of primary antibody at 1/5000 (v/v) gave high absorbance with low IC50 value of 0.0183 ng/mL. Futhermore, 8% skimmed milk produced the lowest background reading and was used as blocking agent. By using multi-level factorial design, an interaction plot between pH, incubation time and incubation temperature was obtained. It can be deduced that pH 7 with 0.5 hour incubation time at 25⁰C was optimal for the competition between primary antibody and free antigen to compete for binding site. From the result, the working range of AFB1 was between 0.001 to 10 ng/mL (R2=0.9875) and the LOD was found at 0.15 pg/mL. A stable fabrication of AFB1- BSA onto the modified SPCE was obtained by activating the carboxylic acid groups using coupling agent, NHS and EDC. AFB1 was quantified indirectly based on the activity of HRP enzyme that caused TMB (ox) to be reduced at potential between 0.2 to 0.3 V, where the peak was detected in electrochemical system. A non-linear calibration curve was plotted with R2 of 0.9873 and IC50 of 0.0015 ng/mL. The linear working range was between 0.0001 to 10 ng/mL with LOD of 0.03 pg/mL. Furthermore, the reproducibility and repeatability of this immunosensor were 4.78% and 2.71%, respectively. The test using spiked peanut sample gave good recovery of 80-127%. As a conclusion, a sensitive immunosensor with MWCNT/CS base electrode was successfully developed for detection of AFB1.